Development of Social Arithmetic Teaching Materials Using IT-Based PMRI Approach for SMP Students - Sharli Yunita Astari; Nila Kesumawati; Misdalina Misdalina (Universitas Sriwijaya, 2021)
This study aimed to develop teaching materials using an IT-based PMRI approach for junior high school students. The type of this research was a research and development model. This study employed the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The teaching materials were validated by material experts and media experts before being tested. In addition, this study involved a student response questionnaire investigating the IT-based teaching materials. The validity of teaching materials revealed an average score of 4.40 determined by the results of the teaching material assessment conducted by two expert lecturers, and an average score of 4.80, determined by the results of the teaching material assessment conducted by mathematics teachers at SMP Negeri 56 Palembang. The practicality of teaching materials (student books) had an average score of 4.27 determined by the students' responses to teaching materials. The results of validating material experts, media experts, subject teachers, and student response questionnaires indicated that the teaching materials developed were valid and practical. Overall, this study has shown that the teaching materials developed are very suitable for learning. In addition, the teaching materials developed can improve student learning outcomes on arithmetics materials.